Linperlisib causing high blood sugar and hyponatremia, leading to facial nerve paralysis and muscle nerve damage: A rare case report - Jiang, Yu-cai; Zhao, Cheng-fei; Zheng, Lin-lin (Medicine (Baltimore), 2025)
Rationale: Linperlisib is a highly selective small-molecule inhibitor of phosphatidylinositol-3-kinase delta for the treatment of relapsed/refractory follicular lymphoma. Patient concerns: The patient was a 64-year-old male with peripheral T-cell lymphoma and diabetes mellitus who experienced hyperglycemia, hyponatremia, facial palsy, and myalgia during linperlisib treatment. Diagnoses: Drug-induced high blood sugar and hyponatremia. Interventions: Active management of hyperglycemia during hospitalization and hyponatremia was corrected with active symptomatic treatment. Outcomes: During hospitalization, the patient's hyperglycemia and hyponatremia were effectively managed through active symptomatic treatment. However, following a reduction in the linperlisib dose, the patient developed recurrent hyperglycemia, hyponatremia, and new-onset myalgia. Consequently, the patient declined further linperlisib therapy and permanently discontinued the medication. Lessons: Clinicians should be aware of the risk of complications such as hyperglycemia and hyponatremia in patients with lymphoma and diabetes receiving linperlisib.